Regenerative capacity of neural tissue scales with changes in tissue mechanics post injury - Carnicer-Lombarte, Alejandro; Barone, Damiano G.; Wronowski, Filip; Malliaras, George G.; Fawcett, James W.; Franze, Kristian (Biomaterials, 2023)
Spinal cord injuries have devastating consequences for humans, as mammalian neurons of the central nervous system (CNS) cannot regenerate. In the peripheral nervous system (PNS), however, neurons may regenerate to restore lost function following injury. While mammalian CNS tissue softens after injury, how PNS tissue mechanics changes in response to mechanical trauma is currently poorly understood. Here we characterised mechanical rat nerve tissue properties before and after in vivo crush and transection injuries using atomic force microscopy-based indentation measurements. Unlike CNS tissue, PNS tissue significantly stiffened after both types of tissue damage. This nerve tissue stiffening strongly correlated with an increase in collagen I levels. Schwann cells, which crucially support PNS regeneration, became more motile and proliferative on stiffer substrates in vitro, suggesting that changes in tissue stiffness may play a key role in facilitating or impeding nervous system regeneration.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Crush injury; Nerve compartments; Nerve injury; Nerve stiffness; Schwann cells; Tissue mechanics